RELAÇÃO MÃE-FILHO E ANEMIA EM CRIANÇAS DE 12 A 36 MESES EM SÃO LUIS-MA: uma contribuição da Coorte Brisa. - COSTA, Luciana Cavalcante (2017)
The mother-child relationship is essential to provide good health conditions in childhood, there is no first year of life, but throughout early childhood to this stage in a critical stage of development, Anemia. Anemia is a global public health problem with important consequences resulting from isolated or multiple causes that act concomitantly and influence a child's health. The objective of this study was verified in relation to the mother-child and the occurrence of anemia in children aged 12-36 months in São Luís. This is study "BRISA cohort, carried out in the cities of São Luís-MA and Ribeirão Preto. The data were collected at the time of birth and did not follow the second year of life (12 to 36 months). 5,166 birth cohort births. For an investigation of anemia, blood collection data were used for 2,213 children. The prevalence of anemia in children aged 12-36 months was 24.0%, and the proposed model showed good adjustment and had no suggestions Plausible modifications (RMSEA = 0.019, CFI = 0.965, TLI = 0.961). The mother-child relationship had no effect on the occurrence of anemia in the child (CF = 0.031, p = 0.377). The study confirms the high prevalence of anemia, underscoring a magnitude of the problem among children living in a capital city in the Brazilian Northeast, but there is no relationship between mother and child.